Legal regulation of technologically improved people in the United States and China - V. Morozov; V. Chukreev; D. Rizayeva (BRICS Law Journal)
As humanity improves its use of technologies that can replace parts of a biological organism with ones containing mechanical or electronic components, it raises important legal and political issues. For example, the successful implantation of devices in human bodies could lead to the emergence of new cognitive and motor abilities, thereby resulting in the creation of a new class of people. Undoubtedly, this new class of people with extraordinary abilities would require a legal and governmental response. However, the question that arises is what legal rights might be given to these people, considering that they are more similar to machines than to men or women. The following legal aspects are of the utmost importance: the legal rights and responsibilities of cyborgs; the regulation of access to neuroprosthetic devices by third parties; and the limitation of the illegal use of the damaging capabilities of cyborgs. This article examines a number of laws and regulations from various jurisdictions in the United States, the European Union, South Korea and China that apply to cyborg technologies, with a particular focus on a legal doctrine that applies to neuroprostheses.